MADONNAS, IDOLS AND CORPSES IN PUSHKIN’S POETIC MYTHOLOGY (Philological Studies, 2019)
The attempt to give new interpretation of the series of poetic structures in Alexander Pushkin's creations (a peculiar “statuary cycle” discovered by R. Jacobson) is made in the article. As an instrument of interpretation the concept of “repetition” (from Freudo-Lacanian analysis) is used. A series of Pushkin’s texts about the statue is considered in its coordination with poetry of the so-called “secret love”. Conclusions are drawn about strengthening of destructive and demonic features of sacred female images of Pushkin poetry of the 1830s and the subject’s metamorphoses in the poetic world.
Keywords: poetic world, psychoanalysis, mystical eros, power, desire